Potential environmental risks associated with biofouling management in salmon aquaculture - O Floerl (Inter-Research, 2016)
The accumulation of biofouling organisms on farm infrastructure is an on-going problem for the global salmon aquaculture industry. Most salmon farmers in production regions worldwide undertake regular in situ net cleaning using specialised high-pressure washing rigs. Generally, the material removed from the net during cleaning is discharged into the surrounding environment. This ‘cleaning waste’ consists predominantly of biofouling organisms (intact and fragmented), but may also contain fish pathogens and antifouling coating particles containing biocides. The suspension, dispersal and deposition of this material are associated with a range of potential risks that can be grouped into 4 main categories: (1) health or disease risks (e.g. direct damage to sensitive tissues upon contact with cleaning waste, and facilitation of infection by pathogens); (2) deposition and pollution risks (impact on benthic communities around farms through deposition of organic material and antifouling biocides); (3) invasive species risks (localised dispersal of non-indigenous propagules and fragments); and (4) biofouling exacerbation (e.g. ‘self-seeding’ of downstream production cages). Here, we describe and discuss these 4 potential risks associated with in situ cleaning and present an agenda and research priorities to better understand and manage these risks.